Assessment of Double‐Crop and Relay‐Intercropping Systems of Peanut with Soft Red Winter Wheat and Residual Herbicides. Issue 1 (27th June 2017) - Moss, Justin W.; Tubbs, R. Scott; Grey, Timothy L.; Smith, Nathan B.; Johnson, Jerry W.
Abstract : Core Ideas: The southern United States has long warm seasons where relay‐intercropping could have benefits. Wheat followed by peanut can be a successful cropping system if managed correctly. Herbicide strategies are important when considering relay‐intercropping systems. Double‐cropping peanut after wheat was more successful than relay‐intercropping. Neither imazapic nor pyroxasulfone caused injury to peanut or Clearfield wheat. Multiple‐cropping systems for peanut ( Arachis hypogaea L.) have potential in the southeastern United States where a prolonged growing season exists. Full‐season soft red winter wheat ( Triticum aestivum L.) production typically pushes peanut planting later than optimum, but a relay‐intercrop (RI) system may allow peanut to be planted on‐time while still harvesting wheat grain. However, practical approaches for weed control in this system must be identified. Project objectives were to determine the most effective cropping systems to maximize wheat and peanut potential and assess efficacy and injury to wheat and peanut following different herbicide programs. Twelve cropping systems included variations of double‐crop (DC), RI, and monocrop (MC) management. Studies were conducted at Tifton and Plains, GA, in 2011 and 2012. The RI treatments averaged 20 to 42% less wheat yield than DC systems. Similarly, peanut yield averaged 20 to 26% less, total sound mature kernels (TSMK) (2–7%) were reduced, and more tomato spotted wilt virus (TSWV) ( Tospovirus ) incidence (4–5%) occurred with earlier planting (RI and traditional MC scenarios) compared with later planting (DC and late MC). There were no differences in wheat yield when sprayed with imazapic compared with nonsprayed, indicating imazapic is not an injury concern in imidazolinone‐resistant wheat. Growers interested in producing peanuts and wheat in the same year would be at an advantage to use a DC system, and have several herbicide options without major risk of injury to wheat or peanut.